2003
DOI: 10.1063/1.1605944
|View full text |Cite
|
Sign up to set email alerts
|

Continuum level treatment of electronic polarization in the framework of molecular simulations of solvation effects

Abstract: The hybrid molecular–continuum model for polar solvation considered in this paper combines the dielectric continuum approximation for treating fast electronic (inertialess) polarization effects and a molecular dynamics (MD) simulation for the slow (inertial) polarization component, including orientational and translational solvent modes. The inertial polarization is generated by average charge distributions of solvent particles, composed of permanent and induced (electronic) components. MD simulations are perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 56 publications
3
72
0
Order By: Relevance
“…However, reasonable value for a model of point charges should be close to 1/ɛitalicel, i.e. about 0.75 (for water ε el =1.78), which results in the value of effective dipole 16-18 μ eff ≃ 2.35 D .…”
Section: Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…However, reasonable value for a model of point charges should be close to 1/ɛitalicel, i.e. about 0.75 (for water ε el =1.78), which results in the value of effective dipole 16-18 μ eff ≃ 2.35 D .…”
Section: Theorymentioning
confidence: 97%
“…The first two terms do not explicitly contribute to intermolecular forces Fi=Uri; however, they need to be included in the potential energy, enthalpy and especially in solvation energy calculations 15,17-18,28-30 . The appearance in theory of these new terms also suggests a new approach for the parameterization of bonded potential.…”
Section: Theorymentioning
confidence: 99%
“…In particular, the dielectric response is very slowly converging in simulations and is potentially affected by approximations made to describe the long-range electrostatic forces. Several simulation protocols in which polarization response is (partially) integrated out by analytical techniques have been proposed [20,21]. Integral equation theories have been successfully applied to small solutes [22], but examples of their application to solvation and reactivity of large solutes are just a few [23].…”
Section: Introductionmentioning
confidence: 99%
“…20 The relations considered above demonstrate the essence of the approach: in condensed state, all polarization effects are reduced to some sort of scaling of the original fixed charges and dipoles of the model. The charge scaling has been discussed earlier on the basis of much simpler and pure intuitive picture [30,31,36]. The present theory provides additional insights and rigor into the question of how the screening factors D() should be selected.…”
Section: Consider a Neutral (Zero Net Charge) Molecular Fragment () Amentioning
confidence: 64%
“…The theory states that if simulations involve only similar configurations so that there is a well-defined average molecular dipole moment or, more generally, a welldefined average charge distribution within the molecule, then a typical set of fixed 30 parameters, such as charges, can be introduced that represent an averaged charge distribution [37]. We showed that the remaining fluctuations of charges around the average can be included as an additional renormalization or uniform scaling of the meanfield parameters [31,32].…”
Section: Discussionmentioning
confidence: 99%